Single phase inverter with wide-input voltage range for solar photovoltaic application - Ibrahim, O. (Institute of Electrical and Electronics Engineers Inc., 2015)
Solar energy is considered as fastest growing renewable energy source after wind energy for electricity generation. Solar energy is a free, clean abundant sun energy considered as inexhaustible source for electricity generation. Solar photovoltaic system is characterised with variable output power due to its operation dependency on solar irradiance and cell temperature. To maximize the energy generation potential of solar PV, research effort is focused on solar cell manufacturing technology to increase its generation efficiency and exploring advancement in power electronic devices for small and large scale deployment. Presented in this paper is a single phase inverter with no transformer for solar PV application. A closed loop DC-DC boost converter that accepts wide input DC voltage from 40 V - 60 V to produce constant 330 V DC voltage is modelled in Matlab/Simulink. An H-bridge 2-level inverter was used to convert the DC voltage to chopped AC voltage which was then filtered to give pure sinusoidal AC of 230 V RMS. The output voltage of the inverter has a very low total harmonic distortion of less than 1 which makes the system suitable for local AC load and grid connection. Â© 2015 IEEE.